The Impact of Phytosterols on the Healthy and Diseased Brain - Dierckx, Tess; Bogie, Jeroen F.J.; Hendriks, Jerome J.A. (Current Medicinal Chemistry, 2019)
The central nervous system (CNS) is the most cholesterol-rich organ in mammals. Cholesterol homeostasis is essential for proper brain functioning and dysregulation of cholesterol metabolism can lead to neurological problems. Multiple sclerosis (MS) and Alzheimer’s disease (AD) are examples of neurological diseases that are characterized by a disturbed cholesterol metabolism. Phytosterols (PS) are plant-derived components that structurally and functionally resemble cholesterol. PS are known for their cholesterol-lowering properties. Due to their ability to reach the brain, researchers have started to investigate the physiological role of PS in the CNS. In this review, the metabolism and function of PS in the diseased and healthy CNS are discussed.
Keywords: central nervous system